Fluoride Ion Conductive Polymer Electrolytes for All-solid-state Fluoride Shuttle Batteries - Keitaro TAKAHASHI; Atsuya YOKOO; Yukari KANEKO; Takeshi ABE; Shiro SEKI (Electrochemistry, 2020)
To control the fluoride dissociation and conduction of polyether-based solid polymer electrolytes, an electrolyte system composed of a host polymer, metal salt, and anion acceptor was proposed. Appropriate choices of metal salt with low lattice enthalpy and anion acceptor concentration were important to obtain polymer electrolytes with high fluoride conductivity. The results of thermal and electrochemical measurements revealed that the optimal electrolyte system displayed a relatively high fluoride conductivity of ca. 1 × 10−6 S cm−1 at 303 K and fluoride transference number of over 0.8 (80%).